1986
DOI: 10.1080/00986448608911346
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Oxidation on Silver Catalysts: Effect of Ethylene Oxide and of External Transfer Limitations

Abstract: Ethylene oxidation to ethylene oxide and to carbon dioxide over silver catalysts was studied in a CSTR. The effects of two factors on the catalyst performance were examined. The first was the presence of excess ethylene oxide in the feed. A kinetic model was introduced which assumed that ethylene and ethylene oxide compete for the same sites on the catalyst surface. This model provided reasonable quantitative agreement with kinetic and potentiometric measurements. The second factor that was studied was the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In the data treatment, the oxidation of ethylene oxide was neglected. As established in previous studies, 12,17 the rate of reaction 3 is expected to be much smaller than that of reactions 1 and 2 under our experimental conditions (i.e., low ethylene conversions and no ethylene oxide in feed) because of competitive adsorption of other components on the active surface.…”
Section: Interpretation Of the Experimental Datasupporting
confidence: 52%
See 1 more Smart Citation
“…In the data treatment, the oxidation of ethylene oxide was neglected. As established in previous studies, 12,17 the rate of reaction 3 is expected to be much smaller than that of reactions 1 and 2 under our experimental conditions (i.e., low ethylene conversions and no ethylene oxide in feed) because of competitive adsorption of other components on the active surface.…”
Section: Interpretation Of the Experimental Datasupporting
confidence: 52%
“…14,15 The same effect is also reported for oxygen partial pressure. 16 In addition, several studies have shown that all product species can inhibit both reactions, [16][17][18][19] but the reported results are sometimes contradictory.…”
Section: Review Of Kinetic Models Available In the Literaturementioning
confidence: 99%
“…In Ref. [2], an inhibition of the epoxidation rate was observed and a slightly higher combustion rate was obtained which was explained by the decomposition of ethene oxide. In Ref.…”
Section: Ethene Oxidementioning
confidence: 96%
“…In Refs. [2] and [g-16], a mechanism is suggested in which molecular oxygen is the active component for epoxidation. However, on the basis of theoretical considerations [3,17] and studies involving special techniques such as IR spectroscopy, temperature-programmed desorption (TPD) and temporal analysis of products (TAP) [7,, and because the selectivities have been reported to be above 85.7% [16,22], mechanisms based on one single adsorbed state of atomic oxygen in both reactions are favoured.…”
Section: Mechanism Of Ethene Epoxidationmentioning
confidence: 99%
See 1 more Smart Citation